High Integrity Low Publicity: Research Performance of Professors in Indonesian State Islamic Universities - Ija Suntana; Tedi Priatna; Dede Kania; Siti Nurfatoni (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2022)
This study aims to analyze the performance of the publihed research results by professors in three State Islamic Universities (UINs). By using the descriptive–qualitative analysis and quantitative data reading, this study analyzes research outputs of lecturers with a full professorship in the State Islamic Universities from January to October 2019. The research finds that most of the professor’s research results were not published whether in the forms of books or scientific journal articles. 60% of the professors have a lack of understanding of the open journal system, which causes a low level of publication among them. One program that is very effective in helping them to increase the productivity of the publications is a program of publication assistance.  The well-versed information technology assistants help the professors to get familiar with the information technology. This study adds to the existing literature regarding the research performance of university professors, especially in understanding what factors that hinder the publication performance of State Islamic University professors in Indonesia.